Ni-doped Co3O4 spheres decorated on CNTs nest-like conductive framework as efficiently stable hybrid anode for Na-ion batteries. Issue 19 (1st October 2021) - Zawar, Sidra; Ali, Ghulam; Afshan, Nousheen; Atiq, Shahid; Mustafa, G.M.; Hasnain, Hamza; Iftikhar, Faiza Jan
Abstract: The proficient realization of Na-ion batteries (NIBs) having exceptional electrochemical behavior is considered to bridge the hurdles triggered by inadequate resources and costly manufacturing of Li-ion batteries. Herein, we report a facile synthesis of Ni0.06 Co2.94 O4 /CNTs hybrid using the solvothermal route and Ni0.06 Co2.94 O4 using the hydrothermal approach. The formation of a nest-like conductive framework of Ni0.06 Co2.94 O4 /CNT composites, aligning favorably to form an assembly of a layered structure, supports an efficient Na-ion insertion/extraction process. A high initial charge capacity of 621 and 582 mAh g -1 is delivered by Ni0.06 Co2.94 O4 /CNTs and Ni0.06 Co2.94 O4 electrodes, respectively which retained up to 328 and 239 mAh g -1 after 100 cycles. The electrodes also delivered excellent rate performance with 119 and 93 mAh g -1 at 5.0C and retained 77 and 64% of initial capacity, respectively when recovered from 0.05C. Additionally, Ni0.06 Co2.94 O4 /CNTs exhibited low impedance over a wide range of frequencies resulting in more Na ions storage and a faster Na insertion/extraction process. The exceptional performance shown by the hybrid electrode is due to the synergistic influence flanked by binary metal oxides and CNTs. Hence, the hybrid of Ni-doped metal oxide and carbonaceous species emerge as an excellent choice for use as an electrode for electrochemical energy storage devices.